Development Of Simulation Control Two Water Supply Pump Using Relay Change Over And Floatless Level Switch - Baliarta, I Nyoman Gede; Sudana, I Made (Proceedings; Vol 1 No 1 (2017): Proceeding IJCST 2017, 2018)
System of water supply pump  must be installed in a building. The purpose of this research is to create the practical module for system of water supplay pump for building. So the students' competence on the utility of the building, especially in the field of water supply pump system can be achieved more easily. This practice module uses 2 pumps, 2 water tanks, 1 as tank as underground tank and 1 again as tower tank. Using WLC (water level control) to control on-off  the pump,  based on the water level in the tower tank. Using Relay Change over to automatically convert the pump on duty. In addition it helps to control the water reservoir automatically so that no empty or empty water holding tanks will be available and maintain the stability of the water distribution in the water holding tank